2011
DOI: 10.1111/j.1538-7836.2010.04082.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact on venous thrombosis risk of newly discovered gene variants associated with FVIII and VWF plasma levels

Abstract: To cite this article: Morange P-E, Saut N, Antoni G, Emmerich J, Tré gouë t D-A. Impact on venous thrombosis risk of newly discovered gene variants associated with FVIII and VWF plasma levels. J Thromb Haemost 2011; 9: 229-31.Through a genome-wide association study (GWAS), seven new single nucleotide polymorphisms (SNPs) were recently found to be associated with plasma levels of factor (F) VIII and von Willebrand Factor (VWF) by the CHARGE consortium [1]. These SNPs were located in five genes that have not p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 5 publications
0
21
0
Order By: Relevance
“…In the MEGA and HVH studies, the rs1039084 serving as a proxy for the STXBP5 rs9390459 was further found associated with VT, the rs1039084‐G allele being associated with decreased risk of the disease, OR approximately 0.90 [38]. A similar trend was observed in the MARTHA study [39] for the rs9390459‐A allele, OR approximately 0.93, but it did not reach statistical significance. This lack of significance could be due to the under‐powered nature of the MARTHA study, which relied on a sample of 1,150 VT cases and 801 controls.…”
Section: Novel Susceptibility Genes For Vt Discovered Through Gwas Apmentioning
confidence: 68%
See 1 more Smart Citation
“…In the MEGA and HVH studies, the rs1039084 serving as a proxy for the STXBP5 rs9390459 was further found associated with VT, the rs1039084‐G allele being associated with decreased risk of the disease, OR approximately 0.90 [38]. A similar trend was observed in the MARTHA study [39] for the rs9390459‐A allele, OR approximately 0.93, but it did not reach statistical significance. This lack of significance could be due to the under‐powered nature of the MARTHA study, which relied on a sample of 1,150 VT cases and 801 controls.…”
Section: Novel Susceptibility Genes For Vt Discovered Through Gwas Apmentioning
confidence: 68%
“…This lack of significance could be due to the under‐powered nature of the MARTHA study, which relied on a sample of 1,150 VT cases and 801 controls. Conversely, the TC2N rs1884841 serving as a proxy for the rs10133762 was associated with VT in the French GWAS sample, MARTHA and FARIVE [39] while no association was observed in the HVH study [38]. In the three French collections gathering 2163 VT patients and 2617 controls, the rs1884841‐T allele with frequency approximately 0.44 was associated with an increased OR for VT of 1.27, this allele corresponding to that associated with increased VWF levels according to CHARGE results [36].…”
Section: Novel Susceptibility Genes For Vt Discovered Through Gwas Apmentioning
confidence: 99%
“…We have recently observed that, among the newly identified vWF and/or FVIII genes by the CHARGE consortium, TC2N could also be associated with VT risk [27]. Therefore we investigated the effect of the SNPs identified in our meta-analysis on the risk of VT. Our working hypothesis was that SNPs associated with increased (decreased, resp.)…”
Section: Resultsmentioning
confidence: 99%
“…Several other polymorphisms/genes have been proposed as risk factors for VTE but these lack compelling evidence, including robust statistical replication in independent studies, to be definitively claimed as susceptibility variants/genes for the disease. These include the rs2232710 of SERPINA10 , which encodes the Protein Z‐Dependent Protease Inhibitor of coagulation factors Xa and XIa (Folsom et al , ; Gorski et al , ); SERPINE1 rs2227631, influencing circulating plasminogen activator inhibitor‐1 (PAI‐1) levels (Huang et al , ); C4BPB/C4BPA rs3813948, affecting PS associated phenotypes (Buil et al , ); the rs7080536 of the HABP2 gene, encoding factor VII (FVII) activating protease (Ahmad‐Nejad et al , ); HIVEP1 rs169713 with, as yet, no associated intermediate phenotype (Morange et al , ); F13A1 rs5985 (Val34Leu) (Wells et al , ), influencing FXIII activity (Kohler et al , ; Wartiovaara et al , ); APOH rs8178847, associated with thrombin generation (Tang et al , ); genetic variations at the STAB 2 , STX2 and TC2N loci with suggestive impact on VTE risk (Germain et al , ; Morange et al , ; Smith et al , ; Desch et al , ) via their influence on VWF levels (Smith et al , ); and the rs4602861 (Germain et al , ; Klarin et al , ) at the ZFPM2 locus, whose suspected association with VTE could involve platelet count (Gieger et al , ) and vascular endothelial growth factor (Debette et al , ). Some of these associations, if true, could be restricted to some specific ethnic populations.…”
Section: Established Venous Thrombosis‐disease Genes and Their Suscepmentioning
confidence: 99%